Hybrid FeWO4-Hyaluronic Acid Nanoparticles as a Targeted Nanotheranostic Agent for Multimodal Imaging-Guided Tumor Photothermal Therapy - Yang C; Che X; Zhang Y; Gu D; Dai G; Shu J; Yang L (International Journal of Nanomedicine, 2023)
Chunmei Yang,1,* Xiaoling Che,1,* Yu Zhang,2 Didi Gu,1 Guidong Dai,1 Jian Shu,1 Lu Yang1 1Department of Radiology, The Affiliated Hospital of Southwest Medical University, Nuclear Medicine and Molecular Imaging Key Laboratory of Sichuan Province, Luzhou, Sichuan Province, People’s Republic of China; 2Department of Radiology, The First People’s Hospital of Yibin, Yibin, 644000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jian Shu; Lu Yang, Department of Radiology, The Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan Province, People’s Republic of China, Tel +86 0830-18980253083 ; +86 0830-2504762, Email shujiannc@163.com; yanglu@swmu.edu.cnBackground: Development of versatile nanoplatform still remains a great challenge due to multistep synthesis and complicated compositions. Therefore, it is significant to develop a facile method to synthesize a nanocomposite to achieve multimodal imaging and even imaging-guided cancer therapeutics.Methods and Results: In our study, hyaluronic acid-functionalized iron (II) tungstate nanoparticles (HA-FeWO4 NPs) were successfully synthesized as a versatile nanoplatform by a facile one-pot hydrothermal procedure. The formed multifunctional HA-FeWO4 NPs were investigated via a series of characterization techniques, which demonstrated good biocompatibility, excellent dispersion, low cytotoxicity, active tumor-targeting ability and high photothermal efficiency. Furthermore, tumor was clearly visualized by HA-FeWO4 NPs with multimodal imaging of infrared thermal imaging, magnetic resonance imaging, computed tomography imaging in 4T1 tumor bearing mice. More importantly, HA-FeWO4 could achieve multimodal imaging-guided photothermal therapy of 4T1 tumors.Conclusion: The constructed HA-FeWO4 NPs have great potential as ideal nanotheranostic agents for multimodal imaging and even imaging-guided cancer theranostics in biological systems.Keywords: theranostics, multimodal imaging, photothermal therapy, diagnostic imaging, nanomedicine